Citizenship and Political Rights: An Analysis of the Laws on the Right to Vote of Citizens in Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Fatiha Nur Laili Azizah; Fadhila Assabili; Eka Rahmadani (Jurnal Restorasi : Hukum dan Politik, 2024)
Citizenship in Indonesia grants essential political rights, including the right to vote, as guaranteed by the 1945 Constitution and Law No. 7 of 2017 on General Elections. Despite these regulations aimed at ensuring equitable political participation, significant challenges persist, particularly for marginalized groups such as persons with disabilities, women, first-time voters, and Indonesian citizens residing abroad. This study employs a doctrinal legal approach and a library research methodology. Data were collected from books, legal statutes, and relevant literature. The analysis incorporates legislative, case, conceptual, historical, and comparative approaches to assess the effectiveness of voting rights regulations and to identify the challenges encountered. The research finds that, although the existing regulations are well-established, the implementation of voting rights faces several challenges. Accessibility for persons with disabilities at polling stations remains inadequate, women's participation in rural areas is often constrained by social norms, and first-time voters suffer from a lack of political education. Indonesian citizens abroad also encounter technical difficulties in voting. The study recommends improving accessibility at polling stations, enhancing women’s empowerment programs, strengthening political education for new voters, and reforming the voting system for expatriates to improve transparency and electoral integrity.